Pupuk Daun sebagai Media Alternatif untuk Induksi Kalus Porang (Amorphophallus muelleri Blume.) - Meliana Ximenes Belo; Wina Dian Savitri; Ida Bagus Made Artadana; Didik Pudji Restanto; Popy Hartatie Hardjo (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Foliar fertilizer with an affordable market price can be utilized as an alternative medium for callus induction in Amorphophallus muelleri Blume. This study aims to compare the concentration of foliar fertilizer used as an alternative medium. This study used different concentrations of foliar fertilizer as culture medium: full strength (3,0 g/L) and half strength (1,5 g/L) as substitutes for Murashige and Skoog (MS) medium. The media were supplemented with plant growth regulators (PGRs) 2,4-D (2,4-Dichlorophenoxyacetic acid) at 1,0 mg/L and BAP (6-Benzylaminopurine) at 0,5 mg/L for callus induction, and the study aimed to assess the effect of foliar fertilizer (Gandasil D) instead of MS (Murashige-Skoog) medium. The study used a completely randomized design with three treatments, and the data were analyzed using ANOVA (Analysis of Variance). If the ANOVA was significant at α=5%, the DMRT (Duncan's Multiple Range Test) was used to determine differences. The results showed that the formulation was Gandasil D (3,0 g/L) + 2,4-D (1,0 mg/L) + BAP (0,5 mg/L). However, it had a lower average increase in callus diameter than the Gandasil D (1,5 g/L) + 2,4-D (1,0 mg/L) + BAP (0,5 mg/L) treatment. Still, it provided a higher average increase in fresh weight and a lower browning percentage. Foliar fertilizer (Gandasil D) can be used as a substitute for MS medium to induce porang callus, but further optimization is needed by adding vitamins and organic compounds to achieve growth comparable to that in MS medium.